Epoxy phosphate resin modified water-based acrylic amino baking varnish and preparation method thereof
By using homemade epoxy phosphate resin and anticorrosion filler in aqueous acrylic amino paint, the problems of insufficient adhesion and poor corrosion resistance of the water-based paint on metal substrates are solved, and better binding and anticorrosion properties are achieved.
Patent Information
- Application Number
- CN202310344186.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-03
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2043-04-03
AI Technical Summary
The existing aqueous acrylic amino paint has insufficient adhesion on the surface of metal substrates such as iron, stainless steel, aluminum alloy, zinc alloy, etc., which affects the corrosion resistance of the coating film.
The water-based acrylic amino paint is modified by homemade epoxy phosphate resin, and anticorrosion filler is added to the paint. The phosphate passivation film is formed by reacting the epoxy phosphate resin with the metal substrate to improve adhesion and corrosion resistance.
It significantly improves the bonding performance and corrosion resistance of water-based paint with metal substrates, and enhances the corrosion resistance and mechanical properties of the paint film.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to an epoxy phosphate resin modified water-based acrylic amino baking varnish and a preparation method thereof. Background Art
[0002] Acrylic amino paint has been widely used in coatings in the automotive, instrumentation, household appliances, hardware and other industries due to its excellent adhesion, high gloss and fullness of the paint film, excellent chemical resistance, heat resistance, corrosion resistance and weather resistance. Due to the current market environmental protection requirements and the country's control of volatile organic compound emissions, acrylic amino paint is gradually becoming water-based in the field of industrial coatings. However, compared with traditional solvent-based products, water-based acrylic amino paint lacks adhesion on the surface of metal substrates such as iron, stainless steel, aluminum alloy, and zinc alloy, thus affecting the corrosion resistance of the coating. Therefore, how to find a water-based paint with good adhesion to the metal substrate and excellent anti-corrosion performance becomes the key. Summary of the invention
[0003] The technical problem to be solved by the present invention is to provide an epoxy phosphate resin modified water-based acrylic amino baking varnish and a preparation method thereof in view of the deficiencies in the prior art. The present invention adopts homemade anti-corrosion fillers and epoxy phosphate for modification, and the prepared baking varnish has good bonding performance with the substrate, excellent anti-corrosion performance, and good mechanical properties.
[0004] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0005] A method for preparing an epoxy phosphate resin modified water-based acrylic amino baking varnish comprises the following steps:
[0006] (1) After epoxy resin and ethylene glycol butyl ether are mixed evenly, the mixture is added into a three-necked round-bottom flask, and the mixture is heated under oil bath conditions. The mixture of concentrated phosphoric acid and ethylene glycol butyl ether is added dropwise into the three-necked round-bottom flask. After the addition is completed, the mixture is stirred under reflux and the reaction is carried out until the acid value of the reaction system remains unchanged. The reaction is stopped, and the reaction solution is cooled to room temperature to obtain epoxy phosphate resin;
[0007] (2) Adding hydroxy acrylic dispersion, amino resin, water, pigments, fillers and additives into a mixer and dispersing them uniformly at high speed, and then grinding them to obtain a water-based acrylic amino paint. Adding the epoxy phosphate resin obtained in step (1) into the water-based acrylic amino paint and dispersing them uniformly at high speed to obtain an epoxy phosphate resin-modified water-based acrylic amino paint.
[0008] As a preferred embodiment of the above technical solution, in step (1), the epoxy resin is bisphenol A epoxy resin, and the resin model is a mixture of one or more of E55, E51, E44, E42, E35, and E20.
[0009] As a preferred embodiment of the above technical solution, in step (1), the temperature of the heat preservation reflux stirring reaction is 100-140° C., and the time of the heat preservation reflux stirring reaction is 2-5 h.
[0010] As a preferred embodiment of the above technical solution, in step (1), the molar ratio of the concentrated phosphoric acid to the epoxy group in the epoxy resin is (0.5-1):1.
[0011] As a preferred embodiment of the above technical solution, in step (1), when the epoxy resin and ethylene glycol butyl ether are mixed, the mass ratio of the epoxy resin to ethylene glycol butyl ether is (1-2):1; when concentrated phosphoric acid and ethylene glycol butyl ether are mixed, the mass ratio of concentrated phosphoric acid to ethylene glycol butyl ether is (0.5-1):1.
[0012] As a preferred embodiment of the above technical solution, in step (2), the solid content of the hydroxyl acrylic dispersion is 38-45%, the hydroxyl content of the hydroxyl acrylic acid is 2-4%, and the amount of the hydroxyl acrylic acid added is 30-60% of the mass of the water-based acrylic amino paint; the mass ratio of the hydroxyl acrylic dispersion to the amino resin is (4-8): 1; the amount of the epoxy phosphate resin added is 1-5% of the mass of the water-based acrylic amino paint; the amount of water added is 10-20% of the mass of the water-based acrylic amino paint, the amount of the pigment and filler added is 7-21.5% of the mass of the water-based acrylic amino paint, and the amount of the additive added is 1-9% of the mass of the water-based acrylic amino paint.
[0013] As a preferred embodiment of the above technical solution, in step (2), an anticorrosive filler is added when preparing the water-based acrylic amino baking varnish, and the amount of the anticorrosive filler added is 2-3% of the mass of the water-based acrylic amino baking varnish; the preparation method of the anticorrosive filler is:
[0014] Step 1: Mix a zinc nitrate hexahydrate aqueous solution and a 2-methylimidazole aqueous solution, then centrifuge, wash the precipitate with anhydrous ethanol and dry it to obtain a ZIF nanosheet; add the ZIF nanosheet into ethanol for dispersion, then add oleic acid imidazoline while stirring to obtain a suspension, treat the suspension under vacuum conditions, then filter, and dry the obtained precipitate at room temperature to obtain a ZIF nanosheet loaded with oleic acid imidazoline;
[0015] Step 2: Disperse the ZIF nanosheets loaded with oleic acid imidazoline in deionized water, then add the sodium tripolyphosphate solution, then slowly add the chitosan solution, stir, and finally centrifuge, and wash the precipitate obtained by centrifugation with deionized water, and dry the precipitate to obtain an anticorrosive filler.
[0016] As a preferred embodiment of the above technical solution, the concentration of the zinc nitrate hexahydrate solution is 0.01-0.015 mmol / ml, the concentration of the 2-methylimidazole aqueous solution is 0.1-0.15 mmol / ml, and the volume ratio of the two is 1:1; the temperature of the mixing treatment is room temperature, and the time is 20-30 hours.
[0017] As a preferred embodiment of the above technical solution, the mass ratio of the ZIF nanosheets and oleic acid imidazoline is 0.5:(2-3); the concentration of the sodium tripolyphosphate solution is 4 mg / ml, and the concentration of the chitosan solution is 6 mg / ml; the dosage ratio of the ZIF nanosheets loaded with oleic acid imidazoline, the sodium tripolyphosphate solution, and the chitosan solution is 0.1g:40ml:40-50ml; the temperature of the stirring treatment is room temperature, and the time is 4-5h.
[0018] The epoxy phosphate resin modified water-based acrylic amino baking varnish in the present invention can be silver powder baking varnish, solid color baking varnish or clear varnish baking varnish.
[0019] The pigment and filler in the present invention can be selected from a mixture of one or more of water-based aluminum silver paste, water-based bentonite, high-pigment carbon black powder, red powder, modified zinc phosphate anti-rust powder, and barium sulfate.
[0020] The auxiliary agent in the present invention is a mixture of one or more of an aqueous substrate wetting agent, an aqueous defoaming agent, an aqueous polyamide wax slurry, an aqueous dispersant, and a film-forming auxiliary agent.
[0021] Due to the adoption of the above technical solution, the present invention has the following beneficial effects:
[0022] The present invention uses a homemade epoxy phosphate resin to modify the water-based acrylic amino baking varnish. Epoxy phosphate is to introduce a phosphoric acid group, an epoxy group and a hydroxyl group into the epoxy resin structure. On the one hand, the activity and cross-linking density of the resin reaction can be improved. On the other hand, the phosphoric acid group with strong corrosion resistance reacts with the metal substrate to form a phosphate passivation film, thereby effectively blocking the corrosion of the metal substrate by external moisture, oxygen, etc., and further improving the corrosion resistance of the paint film. The present invention adds a certain amount of epoxy phosphate resin to the water-based product, which can effectively improve the adhesion and anti-corrosion performance of the paint film to the surface of the metal substrate, thereby promoting the development of water-based products in the field of coatings.
[0023] The present invention also adds an anticorrosive filler to the water-based acrylic amino baking varnish for modification. The anticorrosive filler is a ZIF nanosheet encapsulating oleic acid imidazoline and then wrapped with sodium tripolyphosphate and chitosan. The ZIF nanosheet can be highly dispersed in the baking varnish, which can not only improve the toughness of the baking varnish, but also block certain corrosive media, effectively prevent chloride ions, water molecules and oxygen from directly penetrating the filler, and further prolong the diffusion of corrosive substances, thereby achieving the purpose of anticorrosion. The ZIF nanosheet has a porous structure, and the pores can be used as a container for corrosion inhibitors. The present invention combines oleic acid imidazoline into the pores of the ZIF nanosheet under vacuum conditions, and forms a layer of chitosan film on the surface of the ZIF nanosheet under the crosslinking of sodium tripolyphosphate and chitosan for wrapping. The anticorrosive filler prepared by the present invention will swell when encountering a corrosive electrolyte, so that the loaded oleic acid imidazoline will be quickly released, thereby repairing the corrosion on the surface of the metal substrate, and has a certain corrosion inhibition effect. The baking temperature of the baking varnish film prepared by the invention is 120-180°C, the baking time is 15-60min, the prepared paint film coating has high hardness, high hardness, excellent impact resistance, water resistance, chemical resistance and salt spray resistance, is environmentally friendly and non-toxic, and the preparation method is simple. DETAILED DESCRIPTION
[0024] In order to better understand the present invention, the present invention is further described below by way of examples. The examples are only used to explain the present invention and will not constitute any limitation to the present invention. Example 1
[0025] 30 ml of a 0.013 mmol / ml zinc nitrate hexahydrate aqueous solution and 30 ml of a 0.13 mmol / ml 2-methylimidazole aqueous solution were mixed and treated at room temperature for 24 hours, and then centrifuged. The precipitate was washed with anhydrous ethanol and then dried to obtain ZIF nanosheets; 0.5 g of ZIF nanosheets were added to 50 ml of ethanol for dispersion, and then 2.5 g of oleic acid imidazoline was added while stirring to obtain a suspension, the suspension was placed under vacuum conditions for treatment, and then filtered. The obtained precipitate was dried at room temperature to obtain ZIF nanosheets loaded with oleic acid imidazoline;
[0026] 0.1 g of ZIF nanosheets loaded with oleic acid imidazoline was dispersed in 10 ml of deionized water, and then 40 ml of a 4 mg / ml sodium tripolyphosphate solution was added, followed by slow addition of 50 ml of a 6 mg / ml chitosan solution, and the mixture was stirred at room temperature for 5 h, and finally centrifuged, and the precipitate obtained by centrifugation was washed with deionized water, and the precipitate was dried to obtain an anticorrosive filler;
[0027] Mix bisphenol A epoxy resin E44 and ethylene glycol butyl ether evenly, place in a three-necked round-bottom flask, heat at 130°C for condensation and reflux, mix concentrated phosphoric acid and ethylene glycol butyl ether evenly, and then add dropwise to the above reaction solution, control the molar ratio of concentrated phosphoric acid to epoxy groups in bisphenol A epoxy resin E44 to be 1:1, keep warm at 130°C for 2h after the dropwise addition, cool to obtain epoxy phosphate resin, and set aside;
[0028] The water-based aluminum silver paste and ethylene glycol butyl ether are mixed in a mass ratio of 1:1 and then dispersed evenly at a low speed to obtain a slurry; 60wt% of hydroxy acrylic dispersion, 15wt% of amino resin, 11.3wt% of water, 8wt% of aluminum silver paste, 1.5wt% of water-based polyamide wax slurry, 0.1wt% of water-based substrate wetting agent, 0.1wt% of water-based defoaming agent, 2wt% of epoxy phosphate resin, and 2wt% of anti-corrosion filler are mixed evenly to obtain a water-based metallic silver powder baking paint with excellent adhesion. Example 2
[0029] 30 ml of a 0.013 mmol / ml zinc nitrate hexahydrate aqueous solution and 30 ml of a 0.13 mmol / ml 2-methylimidazole aqueous solution were mixed and treated at room temperature for 25 hours, and then centrifuged. The precipitate was washed with anhydrous ethanol and then dried to obtain ZIF nanosheets; 0.5 g of ZIF nanosheets were added to 50 ml of ethanol for dispersion, and then 2.5 g of oleic acid imidazoline was added while stirring to obtain a suspension, the suspension was placed under vacuum conditions for treatment, and then filtered. The obtained precipitate was dried at room temperature to obtain ZIF nanosheets loaded with oleic acid imidazoline;
[0030] 0.1 g of ZIF nanosheets loaded with oleic acid imidazoline was dispersed in 10 ml of deionized water, and then 40 ml of a 4 mg / ml sodium tripolyphosphate solution was added, followed by slow addition of 50 ml of a 6 mg / ml chitosan solution, and the mixture was stirred at room temperature for 5 h, and finally centrifuged, and the precipitate obtained by centrifugation was washed with deionized water, and the precipitate was dried to obtain an anticorrosive filler;
[0031] Mix bisphenol A epoxy resin E44 and ethylene glycol butyl ether evenly, place in a three-necked round-bottom flask, heat at 130°C for condensation and reflux, mix concentrated phosphoric acid and ethylene glycol butyl ether evenly, and then add dropwise to the above reaction solution, control the molar ratio of concentrated phosphoric acid to epoxy groups in bisphenol A epoxy resin E44 to be 1:1, keep warm at 130°C for 2h after the dropwise addition, cool to obtain epoxy phosphate resin, and set aside;
[0032] 55wt% hydroxy acrylic dispersion, 18.6wt% water, 1wt% aqueous dispersant, 0.1wt% aqueous defoamer, 7wt% red powder and 0.2wt% aqueous bentonite were mixed evenly and ground to a fineness of ≤20μm to obtain a color paste; 10wt% amino resin, 0.1wt% aqueous substrate wetting agent, 5wt% film-forming aid, 1wt% epoxy phosphate resin and 2wt% anticorrosive filler were added to the color paste, mixed evenly and then the viscosity of the system was adjusted to 70-80KU with an aqueous polyurethane thickener to obtain an epoxy phosphate resin modified waterborne acrylic amino baking varnish. Example 3
[0033] 30 ml of a 0.013 mmol / ml zinc nitrate hexahydrate aqueous solution and 30 ml of a 0.13 mmol / ml 2-methylimidazole aqueous solution were mixed and treated at room temperature for 24 hours, and then centrifuged. The precipitate was washed with anhydrous ethanol and then dried to obtain ZIF nanosheets; 0.5 g of ZIF nanosheets were added to 50 ml of ethanol for dispersion, and then 2.5 g of oleic acid imidazoline was added while stirring to obtain a suspension, the suspension was placed under vacuum conditions for treatment, and then filtered, and the obtained precipitate was dried at room temperature to obtain ZIF nanosheets loaded with oleic acid imidazoline;
[0034] 0.1 g of ZIF nanosheets loaded with oleic acid imidazoline was dispersed in 10 ml of deionized water, and then 40 ml of a 4 mg / ml sodium tripolyphosphate solution was added, followed by slow addition of 50 ml of a 6 mg / ml chitosan solution, and the mixture was stirred at room temperature for 5 h, and finally centrifuged, and the precipitate obtained by centrifugation was washed with deionized water, and the precipitate was dried to obtain an anticorrosive filler;
[0035] Mix bisphenol A epoxy resin E44 and ethylene glycol butyl ether evenly, place in a three-necked round-bottom flask, heat at 130°C for condensation and reflux, mix concentrated phosphoric acid and ethylene glycol butyl ether evenly, and then add dropwise to the above reaction solution, control the molar ratio of concentrated phosphoric acid to epoxy groups in bisphenol A epoxy resin E44 to be 1:1, keep warm at 130°C for 2h after the dropwise addition, cool to obtain epoxy phosphate resin, and set aside;
[0036] 40wt% hydroxy acrylic dispersion, 19wt% water, 2wt% water-based dispersant, 0.3wt% water-based defoamer, 3wt% high-pigment carbon black powder, 0.5wt% water-based bentonite, 8wt% modified zinc phosphate anti-rust powder, and 8wt% barium sulfate were mixed evenly and ground to a fineness of ≤20μm to obtain a color paste; 10wt% amino resin, 0.2wt% water-based substrate wetting agent, 5wt% film-forming aid, 2wt% epoxy phosphate resin, and 2wt% anti-corrosion filler were added to the color paste, mixed evenly, and then the system viscosity was adjusted to 70-80KU with a water-based polyurethane thickener to obtain an epoxy phosphate resin modified water-based acrylic amino baking varnish.
[0037] The performance of the epoxy phosphate modified waterborne acrylic amino baking varnish prepared in the above embodiment was tested, and the test results are shown in Table 1.
[0038] Table 1
[0039] Testing standards Example 1 Example 2 Example 3 Glossiness GB / T 9754-2007 >90° >90° >90° Adhesion GB / T 9286-1998 Level 0 Level 0 Level 0 hardness GB / T 6739 ≥2H ≥2H ≥2H Neutral salt spray resistance GB / T 1771-2007 3000h paint film without blistering or peeling 3000h paint film without blistering or peeling 3000h paint film without blistering or peeling Resistance to moisture and heat aging GB / T 1740-2007 3000h paint film without blistering, rusting and peeling 3000h paint film without blistering, rusting and peeling 3000h paint film without blistering, rusting and peeling Xenon lamp aging resistance GB / T16422.2-2014 >500h >500h >500h Impact resistance / cm GB / T 1732-1993 56 55 56
[0040] It can be seen from the above test results that the baking varnish prepared by the present invention has good bonding performance with the substrate, excellent anti-corrosion performance and good mechanical properties.
[0041] In addition, it should be understood that after reading the contents of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.
Claims
1. A method for preparing an epoxy phosphate resin modified water-based acrylic amino baking varnish, characterized in that: The following steps are involved: (1) mixing epoxy resin and ethylene glycol butyl ether uniformly and adding the mixture into a three-necked round-bottom flask, heating under oil bath conditions, and dropping a mixture of concentrated phosphoric acid and ethylene glycol butyl ether into the three-necked round-bottom flask. After the dropping is completed, the mixture is stirred under reflux and reacted until the acid value of the reaction system remains unchanged, stopping the reaction, and cooling the reaction solution to room temperature to obtain an epoxy phosphate resin; (2) adding hydroxy acrylic dispersion, amino resin, anticorrosive filler, water, pigment filler and additives into a mixer and dispersing them uniformly at high speed, then grinding them to obtain a water-based acrylic amino paint, adding the epoxy phosphate resin obtained in step (1) into the water-based acrylic amino paint, and dispersing them uniformly at high speed to obtain an epoxy phosphate resin-modified water-based acrylic amino paint; The amount of the anticorrosive filler added is 2-3% of the mass of the water-based acrylic amino baking varnish; the preparation method of the anticorrosive filler is: Step 1: Mix a zinc nitrate hexahydrate aqueous solution and a 2-methylimidazole aqueous solution, then centrifuge, wash the precipitate with anhydrous ethanol and dry it to obtain a ZIF nanosheet; add the ZIF nanosheet into ethanol for dispersion, then add oleic acid imidazoline while stirring to obtain a suspension, treat the suspension under vacuum conditions, then filter, and dry the obtained precipitate at room temperature to obtain a ZIF nanosheet loaded with oleic acid imidazoline; Step 2, dispersing the ZIF nanosheets loaded with oleic acid imidazoline in deionized water, then adding sodium tripolyphosphate solution, and then slowly adding chitosan solution, stirring, and finally centrifuging, and washing the precipitate obtained by centrifugation with deionized water, and drying the precipitate to obtain an anti-corrosion filler; the mass ratio of the ZIF nanosheets and oleic acid imidazoline is 0.5: (2-3); the concentration of the sodium tripolyphosphate solution is 4 mg / ml, and the concentration of the chitosan solution is 6 mg / ml; the amount ratio of the ZIF nanosheets loaded with oleic acid imidazoline, the sodium tripolyphosphate solution, and the chitosan solution is 0.1g: 40ml: 40-50ml; the temperature of the stirring treatment is room temperature, and the time is 4-5h.
2. The method for preparing an epoxy phosphate resin modified water-based acrylic amino baking varnish according to claim 1, characterized in that: In step (1), the epoxy resin is bisphenol A epoxy resin, and the resin model is a mixture of one or more of E55, E51, E44, E42, E35, and E20.
3. The method for preparing an epoxy phosphate resin modified water-based acrylic amino baking varnish according to claim 1, characterized in that: In step (1), the temperature of the heat preservation reflux stirring reaction is 100-140° C., and the time of the heat preservation reflux stirring reaction is 2-5 hours.
4. The method for preparing an epoxy phosphate resin modified water-based acrylic amino baking varnish according to claim 1, characterized in that: In step (1), the molar ratio of the concentrated phosphoric acid to the epoxy group in the epoxy resin is (0.5-1):
1.
5. The method for preparing an epoxy phosphate resin modified water-based acrylic amino baking varnish according to claim 1, characterized in that: In step (1), when the epoxy resin is mixed with ethylene glycol butyl ether, the mass ratio of the epoxy resin to the ethylene glycol butyl ether is (1-2):1; when the concentrated phosphoric acid is mixed with ethylene glycol butyl ether, the mass ratio of the concentrated phosphoric acid to the ethylene glycol butyl ether is (0.5-1):
1.
6. The method for preparing an epoxy phosphate resin modified water-based acrylic amino baking varnish according to claim 1, characterized in that: In step (2), the solid content of the hydroxyl acrylic dispersion is 38-45%, the hydroxyl content of the hydroxyl acrylic acid is 2-4%, and the amount of the hydroxyl acrylic acid added is 30-60% of the mass of the water-based acrylic amino paint; the mass ratio of the hydroxyl acrylic dispersion to the amino resin is (4-8): 1; the amount of the epoxy phosphate resin added is 1-5% of the mass of the water-based acrylic amino paint; the amount of water added is 10-20% of the mass of the water-based acrylic amino paint, the amount of the pigment and filler added is 7-21.5% of the mass of the water-based acrylic amino paint, and the amount of the additive added is 1-9% of the mass of the water-based acrylic amino paint.
7. The method for preparing an epoxy phosphate resin modified water-based acrylic amino baking varnish according to claim 1, characterized in that: The concentration of the zinc nitrate hexahydrate solution is 0.01-0.015 mmol / ml, the concentration of the 2-methylimidazole aqueous solution is 0.1-0.15 mmol / ml, and the volume ratio of the two is 1:1; the temperature of the mixing treatment is room temperature, and the time is 20-30 hours.
8. An epoxy phosphate resin modified water-based acrylic amino baking varnish, characterized in that: Prepared by the method described in any one of claims 1 to 7.
Citation Information
Patent Citations
Chitosan-metal organic framework compounded pellets and preparation method and application thereof
CN105566660A
Water-based metal high-brightness flash silver baking varnish and preparation method thereof
CN109206998A
Waterborne epoxy coating as well as preparation method and application thereof
CN113088158A